P95 Baseline predictors of response to omalizumab and mepolizumab in severe adult asthma. (12th November 2019) - Natarajan, S; Boddy, C; Murphy, A; Bradding, P; Siddiqui, S
Abstract : Introduction and objectives: Currently three main classes of biologics are licensed for severe asthma treatment in the UK. These classes target IgE (omalizumab) and IL-5/IL-5R (mepolizumab/reslizumab and benralizumab). The stratification factors that identify response to omalizumab and mepolizumab beyond the licensing criteria are poorly understood in clinical practice. However, the GINA 2019 severe asthma guidelines advocate clinical stratification when >1 biologic choice exists. The study aim was to evaluate the clinical characteristics that can predict response to omalizumab and mepolizumab. Methods: Over a prospective period (April 2017 to July 2019) we evaluated 105 patients initiated on biologic treatment (omalizumab n=27 [GINA 4=9, GINA 5=18 (oral corticosteroids (OCS) median (IQR):10 mg (10–15) and mepolizumab n=78 (GINA 4=13, GINA 5=65 (OCS:12.5 mg (10–15)] at a single severe asthma centre. Omalizumab response was assessed at 16 weeks as per NICE recommendations, and on-going response at one year; according to MDT defined response markers. Mepolizumab response was assessed based on NICE criteria at 1 year. We looked at the GINA 2019 treatment selection criteria (omalizumab: blood eosinophils ≥260 cells/µl, FeNO ≥20ppb, childhood-onset asthma and mepolizumab: higher blood eosinophils, more exacerbations in the previous year, adult-onset asthma (≥18 years), nasal polyposis) as baseline stratifiers of early and 1 year response using Receiver operator curve analyses (ROC). Results: 35% of patients were eligible for both biologics based on baseline characteristics. When assessing response to biologics [R+ (responder)/R- (non-responder)]: we identified for omalizumab 80.8%/19.2% (16 weeks), 69.2%/30.8% (1 year) response rates and mepolizumab: 71.8%/21.2% (16 weeks), 75.9%/24.1% (1 year) response rates. None of the GINA 2019 baseline stratifiers were predictive of treatment response. The best predictor of response to omalizumab (AUC:0.810, p=0.054) and mepolizumab (AUC:0.746, p=0.006) was exacerbations in the previous year. Conclusions: We have identified that >1:3 patients are eligible for more than one class of biologic. Treatment failure rates in this highly refractory population at 1 year were relatively high with between 20–30% of patients failing therapy. Only exacerbations in the previous year was a significant predictor of treatment response to both biologics. Therefore, more effective decision support tools are required to guide biologic prescribing in clinical practice.